Ad Libitum Mediterranean and Low‐Fat Diets Both Significantly Reduce Hepatic Steatosis: A Randomized Controlled Trial. Issue 5 (14th October 2018) - Properzi, Catherine; O'Sullivan, Therese A.; Sherriff, Jill L.; Ching, Helena L.; Jeffrey, Garry P.; Buckley, Rachel F.; Tibballs, Jonathan; MacQuillan, Gerry C.; Garas, George; Adams, Leon A.
Abstract : Although diet‐induced weight loss is first‐line treatment for patients with nonalcoholic fatty liver disease (NAFLD), long‐term maintenance is difficult. The optimal diet for improvement in either NAFLD or associated cardiometabolic risk factors, regardless of weight loss, is unknown. We examined the effect of two ad libitum isocaloric diets (Mediterranean [MD] or low fat [LF]) on hepatic steatosis (HS) and cardiometabolic risk factors. Subjects with NAFLD were randomized to a 12‐week blinded dietary intervention (MD vs. LF). HS was determined by magnetic resonance spectroscopy (MRS). From a total of 56 subjects enrolled, 49 completed the intervention and 48 were included for analysis. During the intervention, subjects on the MD had significantly higher total and monounsaturated fat, but lower carbohydrate and sodium, intakes compared to LF subjects ( P < 0.01). At week 12, HS had reduced significantly in both groups ( P < 0.01), and there was no difference in liver fat reduction between groups ( P = 0.32), with mean (SD) relative reductions of 25.0% (±25.3%) in LF and 32.4% (±25.5%) in MD. Liver enzymes also improved significantly in both groups. Weight loss was minimal and not different between groups (–1.6 [±2.1] kg in LF vs –2.1 [±2.5] kg in MD; P = 0.52). Within‐group improvements in Framingham Risk Score (FRS), total cholesterol, serum triglyceride (TG), and glycated hemoglobin (HbA1c) were observed in the MD (all P < 0.05), but not with the LF diet. Adherence was higher for the MD compared to LF (88% vs. 64%; P = 0.048). Conclusion: Ad libitum low‐fat and Mediterranean diets both improve HS to a similar degree.